Красота по-русски: [роман] / Татьяна Алюшина - Алюшина Татьяна Александровна (Еще раз про любовь, 2015)
Экземпляры: (20160902) / Инвентарный номер: 39451 / Цена: 161.54 / Сис.шифр: Р2 / Авт.знак: А 59 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6